Technological change : enhancing the benefits : report (Commonwealth Secretariat LondonGB, 1985)
Analyses the impact of new technologies on the economies and societies of countries, particularly developing countries, and concentrates on economic growth, employment and international trade. Spells out the policy implication of that analysis and considers the principles and experiences of technology policies. Examines areas of international cooperation in technology and suggest a role for the Commonwealth in helping member countries to realise the economic and social benefits which new technologies can bring.
Keywords: TECHNOLOGICAL CHANGE